Pemahaman Masyarakat Tentang Ritual Budaya Mandi Safar (Studi Kasus Masyarakat Desa Teluk Lecah Kecamatan Rupat Kabupaten Bengkalis) - Revi Marsela; Rozita Rozita; Norani Norani (LPPM Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
This study aims to determine the process of carrying out the safar bathing ritual and the understanding of the people of Teluk Lecah Village, Rupat District, Bengkalis Regency about the Safar Bathing Cultural Ritual. This study used a qualitative descriptive method by observing interviews with the people of Teluk Lecah Village, and also using literature study by taking material from published books and journals. Safar Bathing Ritual is one of the ancestral heritage which is considered to be able to resist accidents, natural disasters, and disease outbreaks